(untitled) (Jurnal Teknologi Industri Pertanian, 2024)
Spent bleaching earth (SBE) is a waste from the crude palm oil CPO refining process which contains high oil content, around 20-30%. There are several methods to reduce SBE oil content, one of which is the solvent extraction method. SBE residual oil can be utilized as a raw material for biodiesel. This research aims to determine the mass ratio of SBE and solvent, the optimal temperature for extracting residual oil from SBE, and the potential of residual oil from SBE to be used as biodiesel using a microwave reactor. Residual oil extraction was carried out at varying mass ratios of SBE and solvent (1:2, 1:4, and 1:6) and varying temperatures (26, 40, and 50°C). The treated residual oil was esterified and subjected to transesterification reaction with 15% methanol and 1% KOH for 10 minutes at 60°C using a microwave reactor. The optimal extraction result for residual oil was at a 1:4 ratio and 26°C with a yield of 19.12%. There is also an increase in surface area in deoiled-SBE. The conversion of residual oil from SBE into biodiesel yielded 33.53% with a conversion value of 45.28% and a FAME content of 92.97%. The characteristics of the produced biodiesel meet the Indonesian National Standard (SNI) for biodiesel with density of 0.8674 g/cm3 and viscosity of 5.69 mm2/s. Keywords: extraction, fatty acid, transesterification, yield